A randomized control trial of smoking cessation interventions conducted by dentists - Nurul Asyikin Yahya,; Roslan Saub,; Mariani Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The objective of this study was to assess the effectiveness of the 5A’s smoking cessation intervention (5A’s) to that of brief advice (BA) conducted by dentists. A single-blinded randomized controlled trial was designed to compare the effectiveness of the interventions. Six Dental Public Health specialists were recruited, randomized and trained to participate in this trial. Two hundred and fifty patients were required on both arms. The main outcome measures were biochemically validated self-reported abstinence and behaviour change at 6-months follow-up. The odd of quitters in 5A’s intervention was 3.81 (95% CI: 1.87-7.76; p= 0.00) times higher compared to BA. After controlling other factors, the odds ratio for the 5A’s was 1.90 (95% CI: 0.652-5.547; p=0.24) higher compared to BA. The 5A’s was found to be more effective in initiating positive behaviour change compared to BA. However, after controlling other factors, there was no difference in the effectiveness although the odds ratio was slightly higher in 5A’s.